2023
DOI: 10.1097/cmr.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical evidence of comparable efficacy and toxicity of nivolumab and pembrolizumab in advanced melanoma treatment

Abstract: Pembrolizumab and nivolumab (anty-PD-1 antibody) are commonly used for the treatment of melanoma patients. However, their efficacy and safety have never been directly compared, leaving little guidance for clinicians to select the best therapy. The study included patients with inoperable or metastatic melanoma treated in first line with anti-PD-1 immunotherapy (nivolumab or pembrolizumab). In total 1037 patients were enrolled in the study, 455 (44%) patients were treated with pembrolizumab and 582 (56%) with ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results of this study showed that the median OS was 17.4 months for pembrolizumab and 20 months for nivolumab, while the estimated OS at 2 and 3 years was 42/34% for pembrolizumab and 47/37% for nivolumab. The differences in the OS, PFS, and overall response were not statistically significant in naive patients with metastatic melanoma, confirming the clinician's role in the treatment choice [38].…”
Section: Pembrolizumab Long-term Outcomes and Real-life Datamentioning
confidence: 78%
“…The results of this study showed that the median OS was 17.4 months for pembrolizumab and 20 months for nivolumab, while the estimated OS at 2 and 3 years was 42/34% for pembrolizumab and 47/37% for nivolumab. The differences in the OS, PFS, and overall response were not statistically significant in naive patients with metastatic melanoma, confirming the clinician's role in the treatment choice [38].…”
Section: Pembrolizumab Long-term Outcomes and Real-life Datamentioning
confidence: 78%
“…Since, in the literature, the majority of the available data demonstrated the results of clinical trials, the outcomes of melanoma patients that were treated in "routine" healthcare systems may add valuable details to assess the efficacy of immunotherapy. The clinical work of Cybulska-Stopa et al enrolled 1037 patients with metastatic melanoma; 44% of the patients were treated with pembrolizumab and 56% with nivolumab [15]. They found more prolonged overall and progression-free survival among the nivolumab group; however, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%